In-vivo endocardial and epicardial quantitative comparison of multi-wave based non-invasive inverse electrocardiography. (24th May 2021) - Boonstra, MJ; Roudijk, RW; Van Dam, PM; Van Der Heijden, JF; Asselbergs, FW; Loh, P
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This work was supported by the Dutch Heart Foundation Introduction: Non-invasive mapping of ventricular activation using inverse electrocardiography (iECG) in patients with cardiomyopathy during sinus rhythm, may improve risk stratification for sudden cardiac death. However, iECG is complicated by multiple simultaneous endocardial activation waves (multi-wave) mediated by the His-Purkinje system, especially when the QRS complex is narrow. The activation estimation should be based on a realistic physiological model of the His-Purkinje system combining multiple waves initiated at His-Purkinje associated endocardial locations. Equivalent double layer based iECG provides an estimation of both the endocardial and epicardial surface. To improve accuracy, equivalent double layer based iECG was supplemented with electro-anatomical structures associated with the His-Purkinje system to test initial ventricular activation (Figure, Panel C). Multi-wave iECG local activation timing (LAT) maps and invasive LAT maps during sinus rhythm were quantitatively compared. Purpose: Quantitative comparison of multi-wave iECG in His-Purkinje mediated cardiac activation using invasive activation maps in patients. Methods: Thirteen patients referred for invasive electro-anatomical mapping (EAM) of the endocardial and epicardial surface were included. Prior to EAM, each subject underwent 64 electrode body surface potential mapping, cardiac computed tomography (CT) imaging, and 3D imaging of electrode positions. Anatomical models of the ventricles, lungs and thorax were created using CT images and supplemented with electrode positions (Figure, Panel A-B). Electro-anatomical structures associated with the His-Purkinje system were incorporated in ventricular anatomical models (Figure, Panel C) and multiple simultaneous activation waves were simulated. Invasive endocardial and epicardial LAT maps were quantitatively compared to iECG LAT maps. Invasive EAM LAT maps were quantitatively compared to estimated iECG LAT maps (Figure, Panel D) using inter-map correlation coefficients (CC, Pearson's) and absolute differences (AD). Results: Mean inter-map CC and AD were 0.54 ± 0.19 and 18 ± 7 ms respectively for the epicardial surface (n = 13). Similar to the RV endocardial surface (n = 10, CC = 0.50 ± 0.29, AD = 20 ± 8 ms) and the LV endocardial surface (n = 4, CC = 0.44 ± 0.26, AD = 25 ± 7 ms). Conclusion(s): Quantitative comparison of the multi-wave iECG method showed overall moderate performance. This novel iECG method provides a physiologically more realistic and more robust estimation of sinus rhythm and may serve as a tool for detection of electro-anatomical substrates and risk stratification. Compared to other available non-invasive ECG methods, multi-wave iECG captures His-Purkinje mediated ventricular activation better. This method might also be useful for the accurate detection and localization of structural conduction disorders.